Electrospun hierarchically channeled polyacrylonitrile nanofibrous membrane for wastewater recovery. (10th August 2022) - Lu, Jiqing; Cao, Meilian; He, Xiuwen; Hu, Yi; Bai, Long; Huan, Siqi; Han, Guangping; Cheng, Wanli
Abstract: With urgent demands on sustainable utilization of water resource, high-efficient, easy-to-use, and economic purification membrane for wastewater is highly desired. However, integration of micro/nanostructure into membrane through chemical routes inevitably requires tedious treatments and generate secondary pollution. Herein, an oily wastewater purifier with hierarchically porous channel structures is developed via water etching of sacrificial polyvinylpyrrolidone (PVP) cores within electrospun structured polyacrylonitrile (PAN) nanofibrous membrane. The PAN nanofibrous membrane possesses excellent hydrophilicity and underwater superoleophobicity, which is caused by a synergistic effect of hierarchical channel structures and abundant nanopores on nanofiber surface. The porous channel structures increase the gaps among the fibers, which generates a new permeation path, resulting in a significant increase of the water flux from 2275 to 6700 L/(m 2 ·h). The hierarchically constructed structures facilitate the emulsion demulsification, enabling high separation efficiency for various oil/water emulsions (>97%). This green manufacturing strategy provides a new path for developing next-generation wastewater purification membrane. Graphical abstract: Image 1 Highlights: A hierarchically channeled PAN-based purifier is created via electrospinning and water etching. The porous channel structures enable water storage and drainage for membrane. The flux for pure water using the membrane is up to 6700 L/(m 2 ·h). The membrane facilitates demulsification, reaching >97% separation efficiency for emulsions.